Do Faculty Members Apply the Standards for Developing Gifted Students at Universities? An Exploratory Study - Fathi Abunasser; Rommel AlAli (MDPI AG, 2022)
Many studies indicate the importance of the management and nurturing of giftedness. They also focus on talent development, primarily, where the main objective is enhancing academic abilities. To achieve this goal, it is necessary to explore the reality of faculty members' application of talent development standards; this is necessary for laying the practical foundations to enhance the academic abilities of talented students according to the standards for verifying quality, and for clarifying the skills and concepts that are taught. The current study was based on the opinions of 122 faculty members from Saudi public universities who had experiences with gifted students, whereby they answered the following question: Do faculty members apply the standards for developing gifted students at universities? The data were collected by developing an instrument. The data were analyzed using descriptive statistics that mostly showed the reality of the application of the selected gifted development standards. The results of the perceptions of the faculty members participating in the study showed differences in the application of the proposed gifted development standards according to their academic rank.